2015
DOI: 10.1016/j.nut.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary silicon-enriched spirulina improves early atherosclerosis markers in hamsters on a high-fat diet

Abstract: SES protects against metabolic imbalance, inflammation, oxidative stress, and vascular dysfunction induced by an HF diet, and could prevent the atherogenic processes. Synergistic effects between spirulina and silicon were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Similar results have been obtained by our group when Sp and Sp+Si supplements were tested in obesogenic diet‐fed rats (Vide et al, ). This is also in agreement with our previous study performed on Syrian hamsters, where we reported that supplementation with Sp, enriched or not, provided no protection against liver steatosis (Vidé, Virsolvy, et al, ). However, Yigit et al () have reported that Sp supplementation reduced serum cholesterol and triglyceride levels in rats fed a high‐fat diet to near control levels, with a decrease in the apoptotic index in the groups fed a high fat or a basic diet when supplemented with Sp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results have been obtained by our group when Sp and Sp+Si supplements were tested in obesogenic diet‐fed rats (Vide et al, ). This is also in agreement with our previous study performed on Syrian hamsters, where we reported that supplementation with Sp, enriched or not, provided no protection against liver steatosis (Vidé, Virsolvy, et al, ). However, Yigit et al () have reported that Sp supplementation reduced serum cholesterol and triglyceride levels in rats fed a high‐fat diet to near control levels, with a decrease in the apoptotic index in the groups fed a high fat or a basic diet when supplemented with Sp.…”
Section: Discussionsupporting
confidence: 93%
“…Rare are the studies concerning Sp effect on glucose intolerance in Zucker or in obesogenic diet‐fed rats. In a recent study, Vidé, Virsolvy, et al () have fed syrian hamsters for 12 weeks with an atherogenic diet containing 10% hydrogenated coconut oil and 2 g/kg cholesterol. They reported that Sp intake decreased blood insulin level, whereas blood glucose remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…It also contains many photosynthetic pigments (phycocyanobilin chlorophyll and xanthophyll phytopigments) as reported by Gong et al (2005); Bermejo et al (2008), that makes SA a promising new dietary resource supporting the future production requirements of animals. The SA has various biological activities, impact effects as antioxidant (Kurd and Samavati, 2015), anti-inflammatory (Vide et al, 2015), antiviral, immune-modulatory (Sahan et al, 2015), antitumor (Konickova et al, 2014) and probiotics (Shanmugapriya et al, 2015) properties. In addition, SA is believed to reduce toxicity, increase palatability and digestibility, and protected many organs against many drugs and toxic chemicals (Abdel-Daim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hamster is reported to develop the hyperlipidemic condition as early as seven days (Singh et al 2013) to two weeks of feeding (Ioriya et al 2002;Takenaga et al 2000) with HFHC diet. Additionally, researchers have also reported the ability of this model to develop the fatty streak in the aorta as early as 10 weeks (Asami et al 1999;Huang et al 2015;Vinson et al 2001;Vinson et al 2002) to 12 weeks (Auger et al 2005;Kowala et al 1995a;Vide et al 2015) of feeding with HFHC diet. The percentage of fat and cholesterol added to the diet, as well as the diet duration, is important in the design of a disease model.…”
Section: The Golden-syrian Hamster As Hyperlipidemia and Atheroscleromentioning
confidence: 96%